Spastisite Tedavisi - (:unkn) unknown (My University, 2021)
Spastisite üst motor nöron fonksiyon bozukluğuna bağlı pasif eklem hareketine olan hız bağımlı dirençtir. Serebral palsi, omurilikyaralanmaları başta olmak üzere, santral sinir sistemini etkileyen pek çok hastalık spastisiteye neden olabilir. Fizik tedavi verehabilitasyon, medikal tedaviler, ortopedik cerrahiler ve nöroşirürjikal cerrahiler tedavi seçenekleridir. Spastisite tedavi edilirkenfonksiyonel kayıp yaşanmaması öncelikli amaçlardan olmalıdır. Spastisitenin fokal ya da genel olması ile birlikte, durumun geçiciveya kalıcı olması tedavi seçiminde önemli etkenlerdir. Çocuklarda devam eden büyüme ve gelişme, küçük çocuklarda baklofenpompasının yerleştirileceği alanın olmaması cerrahi seçiminde kendine has zorluklara neden olmaktadır. Cerrahi tedaviler genelolarak lezyon oluşturan yöntemler ve santral sinir sistemine ilaç infüzyonu sağlayan yöntemler olarak ayrılabilir. Selektif dorsalrizotomi ve DREZotomi ile birlikte baklofen pompası yerleştirilmesi en sıklıkla kullanılan cerrahi tedavilerdir.

Spasticity is defined as velocity-dependent resistance to passive movement of a joint. A variety of disorders affecting the central nervous system including cerebral palsy and spinal cord injuries may cause spasticity. Treatment options include physical therapy and rehabilitation, medications, orthopedic surgery, and neurosurgery. Avoiding any impairment of useful muscular tonus and functional loss is of paramount importance. Management must be based on whether spasticity is focal or general and permanent or transient. Ongoing growth and development, and technical problems such as lack of an appropriate site for pump insertion in small children may pose additional difficulties in the treatment of spasticity in childhood. Neurosurgical treatment is usually based on lesioning surgery or central nervous system infusion techniques, namely baclofen pumps. The most commonly used surgical techniques include selective dorsal rhizotomy and DREZotomy together with baclofen pump insertion.
Surgical Treatment of Spasticity